Acoustic ray tracing in the atmosphere: with gravitational effect and attenuation considered - Yang Song; Yuannong Zhang; Chen Zhou; Zhengyu Zhao (Annals of Geophysics, 2014)
An acoustic ray tracing model is developed to take into account the impacts of gravitational field and realistic atmospheric attenuation. Ray tracing equations are deduced from the real part of the dissipative dispersion relation, while the acoustic attenuation coefficient and growth rate in a stratified moving atmosphere are deduced from the imaginary part of the dispersion relation. To account for the non-isothermal effect and realistic attenuation, the buoyancy frequency and the cut-off frequency are substituted by the values in the slowly varying atmosphere, and the attenuation coefficient is corrected by the realistic absorption. In the validation by numerical experiment, the ray trajectory obtained by this ray tracing model agrees well with the result calculated by the FDTD method. It is shown that the acoustic trajectory can be accurately predicted by this ray tracing model. The numerical results for 5 Hz acoustic waves show that in the stratospheric ducting the gravitational effect plays a leading role while the attenuation effect could be neglected. But for the thermospheric ducting, the contribution of the absorption becomes more important.